The physiology of fishes. - Varley, Margaret E. (Margaret Elizabeth), 1918-2009 (Academic Press Inc., Publishers, 1957)
The Physiology of Fishes, Volume II: Behavior focuses on the physiology of fishes, as well as nervous and visual systems, sense organs, fish behavior, and pigment of fishes. The book first offers information on the nervous system, including the telencephalon, mesencephalon, metencephalon, medulla oblongata and spinal cord, autonomic nervous system, and functional development of the nervous system. The manuscript then elaborates on the sense organs, acoustico-lateralis system, and olfactory and gustatory senses of fishes. Discussions focus on component parts of the visual system, photoreceptive.